2015
DOI: 10.1016/j.jenvman.2015.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Recreational trails as a source of negative impacts on the persistence of keystone species and facilitation

Abstract: Hiking trails, which are among the most common forms of infrastructure created for nature-based tourism, can alter key ecological processes. Trails can damage plants that facilitate the establishment and growth of other species leading to changes in community and functional composition. This can be a particular concern in harsh alpine ecosystems where plant communities are often dominated by one or two keystone species that provide shelter to a suite of beneficiary species. We analysed how a hiking trail affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 55 publications
0
18
1
Order By: Relevance
“…Although other studies have showed that disturbance can negatively affect nurse plant abundance, size, and density (e.g., Ballantyne & Pickering, ,), we are not aware of other studies that have examined responses in cushion plant size structure and reproduction to relatively high disturbance levels. However, past studies also point to changes in abundance and percent cover.…”
Section: Discussionmentioning
confidence: 87%
“…Although other studies have showed that disturbance can negatively affect nurse plant abundance, size, and density (e.g., Ballantyne & Pickering, ,), we are not aware of other studies that have examined responses in cushion plant size structure and reproduction to relatively high disturbance levels. However, past studies also point to changes in abundance and percent cover.…”
Section: Discussionmentioning
confidence: 87%
“…Additional structural studies could look at the effects of trails on the density of trees, loss of key resources such as hollow-bearing and mature trees, and changes in litter layers. Functional studies could assess how trails affect fire regimes, competition, facilitation, dispersal, pollination and plant-soil feedback loops (Ballantyne and Pickering, 2015b).…”
Section: Need For More Research On Ecosystem Structure and Functioningmentioning
confidence: 99%
“…In negative interactions, one species may reduce the survival, growth and/or reproduction of another through, for example, competition or allelopathy, whereas in positive interactions, the presence of a species facilitates other species through the provisioning of resources or amelioration of stresses or disturbances (Jones et al ., , ; Tilman, ; Aerts, ; Bruno et al ., ; Brooker et al ., ; Filazzola & Lortie, ). Such interactions may significantly affect the composition of communities (Cavieres & Badano, ; le Roux et al ., ; McIntire & Fajardo, ) and thus also potentially alter spatial biodiversity patterns (Araújo & Luoto, ; Meier et al ., ; Cavieres et al ., ; Ballantyne & Pickering, ; Michalet et al ., ; Mod et al ., ).…”
Section: Introductionmentioning
confidence: 99%